2005
DOI: 10.1016/j.ymthe.2004.12.021
|View full text |Cite
|
Sign up to set email alerts
|

mda-7/IL24 kills pancreatic cancer cells by inhibition of the Wnt/PI3K signaling pathways: Identification of IL-20 receptor-mediated bystander activity against pancreatic cancer

Abstract: The melanoma differentiation-associated gene (mda-7; approved gene symbol IL24) is a tumor suppressor gene whose protein expression in normal cells is restricted to the immune system and to melanocytes. Recent studies have shown that mda-7 gene transfer inhibits cell growth and induces apoptosis in melanoma, lung cancer, breast cancer, and other tumor types through activation of various intracellular signaling pathways. In the current study, we demonstrate that Ad-mda7 transduction of human pancreatic cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 38 publications
5
59
3
Order By: Relevance
“…In contrast, a complete set of IL-20/ IL-22 receptor mRNAs was not present in A549 cells (Figure 7a). This finding, relative to A549 not containing a full complement of IL-20/IL-22 receptors, is in agreement with a recent report by Chada et al (2005).…”
Section: Bystander Activity Is Dependent On the Presence Of Il-20/il-supporting
confidence: 93%
“…In contrast, a complete set of IL-20/ IL-22 receptor mRNAs was not present in A549 cells (Figure 7a). This finding, relative to A549 not containing a full complement of IL-20/IL-22 receptors, is in agreement with a recent report by Chada et al (2005).…”
Section: Bystander Activity Is Dependent On the Presence Of Il-20/il-supporting
confidence: 93%
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 80%
“…25,28,31 Furthermore, the results of a Phase I dose-escalation clinical trial using intratumoral delivery of MDA-7 (INGN 241) in patients with advanced cancers, including breast cancer, has shown apoptotic effects in a large volume of tumor and immunoactivating events that are consistent with the pre-clinical tumor suppressor activities of MDA-7/IL-24. 32 We hypothesized that the combination of Ad-mda7 and Herceptin would result in enhanced antitumor activity and thus evaluated the combination of Herceptin with the Ad-mda7 gene drug. In this study, we demonstrate that expression of MDA-7 induces dramatic enhancement of the apoptotic and tumor-suppressing capacities of Herceptin, compared to its use as a single agent.…”
Section: Introductionmentioning
confidence: 99%
“…While our studies identified pancreatic cancer cells to be resistant to Ad.mda-7, another report showed that Ad.mda-7 infection could elicit apoptosis in these cells [101]. This difference may reflect variations in the viral titers and/or vector constructs employed by the two groups.…”
Section: Mda-7/il-24 and β-Catenin And Pi3k Pathwaymentioning
confidence: 62%